What drives the dynamics of employment growth in firms? Evidence from East Africa - Blessing Atwine; Ibrahim Mike Okumu; John Bosco Nnyanzi (Journal of Innovation and Entrepreneurship, 2023)
This study examines the firm level drivers of employment growth in East Africa in which they are categorized as firm specific, entrepreneur specific and business environment characteristics. Using a cross-sectional World Bank Enterprise survey dataset and pooled Ordinary Least Squares estimation (OLS), the results indicate that; (1) employment growth is significantly associated with firm specific characteristics (employment growth is positively related to firm size and innovation while it is negatively associated with the age of the firm), (2) a weak business environment characterized by electricity outages, informal payments and poor court system undermines the firm's ability to contribute to employment growth while strong business environment such as access to finance is positively associated with employment growth (3) employment growth is also positively influenced by managerial experience. Policy recommendations are suggested.
Keywords: L26; D2; J2; O3; O5; 650; Business environment; East Africa; Employment growth; Entrepreneur; Firm